YouBelong Home: A Ugandan community mental health intervention - Cappo, D; Mutamba, B; Ayesiga, K; Kebirungi, E; Chelangat, D; Fegan, G; Jacob, ST; Nsangi, E; Ntabazi, I; Nalubwama, D; Nakasujja, N; Odoki, E; et al. (Springer, 2022)

(untitled)
In Uganda, low resources for mental health provision combine with disadvantage and inadequate supports for family and community-based care. Catalysed by the need to reduce overcrowded psychiatric hospital wards and frequent readmissions at Butabika National Referral Mental Hospital (BNRMH) in Kampala, the nongovernment organisation YouBelong Uganda (YBU) developed the YouBelong Home (YBH) intervention. YBH is a theoretically eclectic pre and post hospital discharge intervention. This paper reports on qualitative findings of the project Curtailing Hospital Readmissions for Patients with Severe Mental Illness in Africa (CHaRISMA), which explored how to refine the YBH intervention. The project was funded by a UK Joint Global Health Trials (JGHT) Development Grant. Data was collected through structured interviews with service users and caregivers, reflective practice by the YBH implementing team and a stakeholder focus group. A summary of refinements to the YBH intervention follows the TIDieR format (Template for Intervention Description and Replication).